Modeling and parameter analysis of deflection of a beam - Pokhrel, Puskar Raj; Lamsal, Bhabani (BIBECHANA, 2021)
In this paper, we present the model equation of a beam when it applies compression forces on ends of the beam and carries a load. From the structural point of view, there should be a suitable model to understand the behavior under different conditions of loading of a beam. Mathematical modeling is the simulation of a physical structure or physical phenomenon by constructing suitable analytic and numerical solutions. We analyze the deflections of the beam by taking different structures of the beam. The structures of the beam depending on the compression forces on beams with different beams with different weights. We observe the deflection by applying various compression forces at the ends of the beam. The influence of the effect of some parameters appeared in mathematical formulations such as area moment of inertia (I), Young’s modulus (E), load (W), and compressive force (P) on deflection variation are investigated in this paper. We analyze the results that how compression forces affect the system. We use the finite difference method to solve the model equation numerically. We analyze and compare the numerical result with the analytic solution. BIBECHANA 18 (1) (2021) 75-82